Training on Identification of Ioded Salt for Members of Nasyiatul 'Aisyiyah Moyudan and Seyegan Sleman Yogyakarta - Yeni Rahmawati; Nazula Rahma Shafriani (Peneliti Teknologi Teknik Indonesia, 2021)
The use of iodized salt in the community is still not optimal. This causes disorders Due to Iodine Deficiency (IDD) in Indonesia is still a major nutritional problem. The impact of iodine deficiency will cause disturbances in the nerves, growth hormone does not work perfectly, and goiter will arise. This is the background for community service activities to provide education related to the use of iodized salt in the household for members of Nasyiatul 'Aisyiyah Moyudan and Seyegan Branches. The method of carrying out activities is carried out online using a whatsapp group due to the COVID-19 pandemic. Service participants were given education about iodized salt, training on identification of iodized salt in the household, monitoring and evaluation of community service activities. The service participants are 20 people. This activity received a positive response from PCNA Seyegan and PCNA Moyudan. The results of the evaluation of this community service activity have increased from the pre test and post test. The average pre-test result is 74.29 and the post-test result is 92.86. The conclusion from the community service activities carried out was that there was an increase in the knowledge and skills of the average participant by 25% on the importance of iodized salt and its simple identification.